DAYA HAMBAT EKSTRAK DAUN CABE JAWA (Piper retrofractum Vahl.) TERHADAP PERTUMBUHAN Staphylococcus aureus - Krisnawan, I Putu Gede; Ari Sandhi W, Putu; Selamet Duniaji, Agus (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 6 No 2 (2017): Jurnal ITEPA, 2017)
The research aimed to test the inhibition of javaneese pepper leaf extract (Piper retrofractum Vahl.) using distilled solvent to the growth of Staphylococcus aureus and to determine the best concentration of the javaneese pepper leaf extract can inhibit the growth of S.aureus. This research uses a Completely Randomized Design (RAL) using 5 treatments javaneese pepper leaf extract concentration of 20%, 35%, 50%, 65%, and 80% with 3 repetitions. Inhibition testing method using the discs to determine the diameter of the growth inhibition of S.aureus. The results of this research showed that all treatments give an inhibition effect 1.40; 2.38; 2.88; 3.76 and 4.4 mm respectivily. The best consentration treatment uses produced 4.49 mm diameter inhibition of 80% extract.On findings candidate phytochemical screening test showed that the leaf extract of javaneese pepper has active compounds such as saponins and flavonoids, as well as the findings Testing The levels of flavonoids have the highest levels of flavonoids are at treatment concentrations of 80% is equal to 222. 567 ppm.